The Casual Nexus of Banking Sector Development and Poverty Reduction - Uddin, Gazi Salah; Kyophilavong, Phouphet; Sydee, Nasim (International Journal of Economics and Financial Issues, 2012)
The paper aims to investigate the inter-temporal causal relationship between banking sector development and poverty reduction in Bangladesh from 1976 to 2010. We have applied new methods using modern time series econometrics techniques based on simulations that are robust to the violation of statistical assumptions, especially when the sample size is small, as is the case in this paper. The results reveal that there is a long-term equilibrium relationship between banking sector development and poverty reduction in the case of Bangladesh. Surprisingly, poverty reduction appears to be a long-term forcing variable to the explanation of Bangladesh’s banking sector development. There is bidirectional causality between these variables. The diagnostic tests show that the underlying desirable assumptions are fulfilled. Time series data on poverty in many developing countries, particularly in Bangladesh, is scant and inadequate. The empirical results of this study will help policy makers determine whether poverty reduction in Bangladesh is a spur to financial sector development. This implies that, in the long term, Bangladeshi policy makers can influence the reduction of poverty through financial sector development. Although several attempts have been made to investigate the relationship between financial development and growth, this paper is the first of its kind to empirically examine the causal relationship between poverty and the development of the banking sector in Bangladesh. Keywords: Poverty; Banking Sector Development; Cointegration; Error Correction; ARDL Bounds Testing; Bangladesh JEL Classifications: C32; F24; F43